HUBUNGAN PARTISIPASI MASYARAKAT DENGAN KEBERFUNGSIAN TEMPAT PENGELOLAAN SAMPAH TERPADU (TPST) SAEMAN PADANGSARI, KOTA SEMARANG - Rifcha Rahmi Zahara; Tri Joko; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Garbage is currently a key issue in large cities, especially in Indonesia. To reduce waste generation in urban conducted flagship program 3R (Reduce, Reuse, Recycle) are expected waste generation can be reduced or even not left at all. The general requirements for waste management one of them is in terms of public participation aspects. This study aimed determine the relationship between community participation with the functioning IWMS Saeman Padangsari, Semarang. This study was observational analytic with cross sectional approach. Samples in this research were 38 respondent. The results showed that there was a relationship of public participation in segregation from the source to the functioning IWMS Saeman, there is a relationship of community participation in waste management using the concept of 3R with functioning IWMS Saeman, there is public participation in relation to pay contributions to the functioning of IWMS Saeman, there is no relationship of public participation in comply with the rules of landfills that have been assigned to the functioning IWMS Saeman, there is no relationship of community participation in maintaining the cleanliness of the surrounding environment with functioning IWMS Saeman, there is a relationship of community participation in an active role in the socialization of environmental waste management with the functioning IWMS Saeman. The need to increase people's active participation in waste management in the region IWMS Saeman Padangsari and increasing the dissemination of the manager IWMS Saeman are several alternatives that IWMS Saeman Padangsari function properly.